Fetal cardiac evaluation services for low‐risk pregnancies: how can we improve?. (1st June 2020) - Yagel, S.; Moon‐Grady, A. J.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2020; 55:747-757 Abstract : Linked Comment: Ultrasound Obstet Gynecol 2020; 55:747-757